Relevance Of Using The Edge Component In Teaching Biology - M. K, Ramazanova; A. A., Kitapbaeva (International Journal of Educational Research & Social Sciences, 2025)
This article discusses the importance and relevance of using edge components in biology education. During the educational process, students will be given a diagnostic survey to get acquainted with the rare plants of their region and determine the level of knowledge of the regional material by students of the Sarsen Amanzholov Higher College. The local history work contains data reflecting the natural, economic, social and cultural interrelation of the region under study. In addition, the most effective way of rational consideration of regional components in unity is to consider the scientific worldview of students, a holistic image of the environment, scientifically based environmental and socio-cultural attitudes, and a system of value-oriented relations.